PENDIDIKAN AGAMA ISLAM DALAM PERSPEKTIF FILSAFAT: ANTARA CITA DAN FAKTA - Majid, Mohamad Arif (IAIN Kediri, 2015)
Islamic education is a long life process in digging and performing Islamic values of (raÃ¡Â¸Â¥matan li al-Ã¢â‚¬â„¢alamÃ„Â«n).Ã‚Â It is also long-life attempts to excavate raÃ¡Â¸Â¥matan values amid the challenges of modernity and thoughts. ThisÃ‚Â article discusses Islamic education from a philosophical perspective. This study found that ontologically theessence of Islamic education is on the process, while epestemoligically it requires the interaction between ratioÃ‚Â and revelation. Axiologically, Islamic education should bring dignity, prominence, and happiness both in theÃ‚Â word and the hereafter. This is what the so-called a Ã¢â‚¬Ëœtwo in oneÃ¢â‚¬â„¢ concept and the key is Ã¢â‚¬ËœlillÃ„Âh.Keywords: Pendidikan Agama Islam, Filsafat, RaÃ¡Â¸Â¥matan li al-Ã¢â‚¬â„¢AlamÃ„Â«n